Approximation to the physical and anthropometric profile in dinghy sailing, in the Optimist class sailors. Study of cases - Tejada-Medina, V.; Ventaja-Cruz, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of this study is to determine the physical profile of the Optimist sailor, by performing a series of physical tests (SJ, flexibility and manual dynamometry) and body composition (weight, height, skinfolds and muscle perimeters), describing the behavior of the selected indicators and assessing the predictive nature of them, for a possible justification of the existence of a sports talent in Dinghy Optimist. Three sailors have been studied, occupying the first three positions of the provincial ranking of the Autonomous City of Melilla. A descriptive correlational design was used. The sailors presented the following descriptive values ​​of body composition: height (149.6 ± 2.16 cm), weight (35.6 ± 3.67 kg), BMI (15.93 ± 2.04) and% GC (7,86 ± 5.31). Regarding the functional characteristics, the values ​​were: SJ hcg (22.53 ± 1.68 cm), SJ tv (428.6 ± 16.28 sg), flexibility (31.67±1,15) and DI dynamometry (23.83 ± 2.02, 20.33 ± 1.25). The results do not show a significant relationship between the variables of body composition and the physical tests performed.